Rapid detection of aflatoxin B1 in paddy rice as analytical quality assessment by near infrared spectroscopy - Qiang, Zhang; Fuguo, Jia; Chenghai, Liu; Jingkun, Sun; Xianzhe, Zheng (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: A rapid identification method for aflatoxin B1 in paddy rice samples was developed by using near infrared spectroscopy under a wavelength range of 1 000-2 500 nm. Eighty paddy rice samples were collected from both natural and artificial infection with aflatoxin B1 to build the calibration models based on the partial least square regression method. The best predictive model to detect aflatoxin B1 in paddy rice was obtained using standard normal variate detrending spectra, with a correlation of 0.850, and a standard error of prediction of 3.211%. Therefore, the result showed that near infrared spectroscopy could be a useful instrumental method for determining aflatoxin B1 in paddy rice. The near infrared spectroscopy methodology can be applied to the monitoring of aflatoxin fungal contamination in postharvest paddy rice during storage and may become a powerful tool for the safety of grain and grain products. Keywords: near infrared spectroscopy, aflatoxin B1, paddy rice, partial least square regression DOI: 10.3965/j.ijabe.20140704.014 Citation: Zhang Q, Jia F G, Liu C H, Sun J K, Zheng X Z. Rapid detection of aflatoxin B1 in paddy rice as analytical quality assessment by near infrared spectroscopy. Int J Agric & Biol Eng, 2014; 7(4): 127－133.